2021
DOI: 10.1093/eurheartj/ehab724.2669
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing in COVID-19 patients at 3 months follow-up

Abstract: Background Long-term effects of Coronavirus Disease of 2019 (COVID-19) and their sustainability are of the utmost relevance. For the chronic phase, the main concerns are the development of pulmonary interstitial disease and/or lingering cardiovascular involvement. How to intercept, assess, and treat these patients with long-term consequences of COVID-19 remains uncertain. Purpose We aimed to determine: 1) functional capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Kardiopulmonale Belastungstests bei 200 Patienten 3 Monate nach akuter COVID-19 zeigten, dass etwa die Hälfte der COVID-19-Überlebenden eine signifikant reduzierte Spitzen-Sauerstoffaufnahme (VO 2peak ) hatte [ 22 , 23 ]. Bei fast einem Drittel (31/99) der Patienten mit reduzierter VO 2peak war dies wahrscheinlich auf ein gewisses Maß an Muskelschwäche zurückzuführen, da die maximale Kraft der Streckung des dominanten Beins unabhängig mit der VO 2peak assoziiert war.…”
Section: Diskussionunclassified
“…Kardiopulmonale Belastungstests bei 200 Patienten 3 Monate nach akuter COVID-19 zeigten, dass etwa die Hälfte der COVID-19-Überlebenden eine signifikant reduzierte Spitzen-Sauerstoffaufnahme (VO 2peak ) hatte [ 22 , 23 ]. Bei fast einem Drittel (31/99) der Patienten mit reduzierter VO 2peak war dies wahrscheinlich auf ein gewisses Maß an Muskelschwäche zurückzuführen, da die maximale Kraft der Streckung des dominanten Beins unabhängig mit der VO 2peak assoziiert war.…”
Section: Diskussionunclassified
“…Cardiopulmonary exercise testing in 200 patients, 3 months after acute COVID-19, revealed that about half of COVID-19 survivors had a significantly reduced peak oxygen uptake (VO 2peak ) [22,23]. In nearly one third (31/99) of patients with reduced VO 2peak , this was probably due to some degree of muscle impairment, as dominant leg extension maximal strength was independently associated with VO 2peak .…”
Section: Respiratory Muscle Impairment Can Be Improved By Inspiratory...mentioning
confidence: 99%
“…Furthermore, athletes, who mostly do not have comorbidities, can be seriously affected by COVID-19 [5,6]. In addition, symptoms can also occur for the first time after recovery from the infection [1], resulting in a lower performance capability of patients and athletes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%